STUDI LITERATUR PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KUALITAS GURU SEKOLAH MENENGAH ATAS: A Literature Review on the Influence of School Principals’ Leadership Styles on the Quality of High School Teachers - Agustini, Mega; Fitri, Lisa; Mutmainah, Mutmainah; Uda, Tonich; Berkat, Berkat (Ganec Swara, 2025)
This study employs a systematic literature review method to analyze the influence of principal leadership styles on the quality of Senior High School (SMA) teachers. The literature review was conducted on articles published during 2015-2024 through academic databases such as Google Scholar, Portal Garuda, and ResearchGate. The analysis results indicate that principal leadership styles have a significant influence on teacher quality, encompassing pedagogical, professional, social, and personality competencies. Democratic leadership style emerges as the most dominant and effective approach due to its ability to create high teacher engagement, while transformational style proves effective in enhancing teacher motivation and professional development. Transactional style demonstrates effectiveness in building work discipline through reward and punishment systems. This research confirms that the combination of leadership style, school work climate, and teacher work spirit simultaneously provides optimal impact on improving teacher performance. The conclusions indicate the need for implementing flexible and situational leadership approaches that align with school characteristics and teachers' professional development needs